2016
DOI: 10.1161/circep.116.003968
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intravenous Magnesium in Facilitating Cardioversion of Atrial Fibrillation

Abstract: P atients with atrial fibrillation (AF) may require electric cardioversion, either because of intolerable symptoms related to AF or as part of a rhythm control strategy. See Editorial by KotechaElectric cardioversion using a biphasic waveform has a procedural success rate of 86% to 94%, sometimes requiring multiple shocks.1-3 The success of electric cardioversion depends on the duration of AF, transthoracic impedance, delivered energy, and the type of electric shock used.1 Pharmacological cardioversion using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…This was demonstrated in another large community cohort where the association of hypomagnesemia with incident AF was identified in long-term follow-up, but not present within the first 90 days. 9 In this issue of Circulation: Arrhythmia and Electro physiology, Rajagopalan et al 10 add to the growing evidencebase on this issue by performing a randomized, double-blind, placebo-controlled trial of intravenous magnesium before electric cardioversion of AF. A total of 261 patients were enrolled with normal magnesium levels at baseline (2.1±0.2 mg/dL; 0.86±0.08 mmol/L).…”
Section: See Article By Rajagopalan Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…This was demonstrated in another large community cohort where the association of hypomagnesemia with incident AF was identified in long-term follow-up, but not present within the first 90 days. 9 In this issue of Circulation: Arrhythmia and Electro physiology, Rajagopalan et al 10 add to the growing evidencebase on this issue by performing a randomized, double-blind, placebo-controlled trial of intravenous magnesium before electric cardioversion of AF. A total of 261 patients were enrolled with normal magnesium levels at baseline (2.1±0.2 mg/dL; 0.86±0.08 mmol/L).…”
Section: See Article By Rajagopalan Et Almentioning
confidence: 99%
“…The Figure displays trials and meta-analyses that have randomized patients to magnesium in a range of situations, including treatment of acute AF, prevention of AF during cardiac surgery, and facilitation of electric cardioversion. [10][11][12][13][14] Although varying with respect to population and magnesium dosage, they share common features of a small sample size, short follow-up, and disappointing treatment effect.…”
Section: See Article By Rajagopalan Et Almentioning
confidence: 99%
“…It has been reported that Mg may have a role in AF prevention in the postoperative cardiothoracic surgery setting . However, there is conflicting evidence regarding the efficacy of Mg in AF treatment in the ED and other settings . As many of these studies had methodological limitations, there is no high‐level evidence to support the use of Mg for the treatment of AF in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis of studies using magnesium to treat AF did not show any significant effect on restoring sinus rhythm compared to placebo, although magnesium reduced the fast ventricular response, when used as adjunct to digitalis (88), or combinations of magnesium, potassium, insulin and glucose (89). A more recent randomized controlled trial (RCT) of infusing magnesium in patients undergoing electric cardioversion for chronic AF, also did not show any increased rate of successful cardioversion (90). As such, role of magnesium in the treatment of AF remains controversial.…”
Section: Arrhythmiamentioning
confidence: 99%